Gap junctions and connexin hemichannels underpin hemostasis and thrombosis. - Vaiyapuri, S; Jones, C; Sasikumar, P; Moraes, L; Munger, S; Wright, JR; Ali, MS; Sage, T; Kaiser, W; Tucker, K; Stain, C; Bye, A; et al. (2012)
BACKGROUND: Connexins are a widespread family of membrane proteins that assemble into hexameric hemichannels, also known as connexons. Connexons regulate membrane permeability in individual cells or couple between adjacent cells to form gap junctions and thereby provide a pathway for regulated intercellular communication. We have examined the role of connexins in platelets, blood cells that circulate in isolation but on tissue injury adhere to each other and the vessel wall to prevent blood loss and to facilitate wound repair. METHODS AND RESULTS: We report the presence of connexins in platelets, notably connexin37, and that the formation of gap junctions within platelet thrombi is required for the control of clot retraction. Inhibition of connexin function modulated a range of platelet functional responses before platelet-platelet contact and reduced laser-induced thrombosis in vivo in mice. Deletion of the Cx37 gene (Gja4) in transgenic mice reduced platelet aggregation, fibrinogen binding, granule secretion, and clot retraction, indicating an important role for connexin37 hemichannels and gap junctions in platelet thrombus function. CONCLUSIONS: Together, these data demonstrate that platelet gap junctions and hemichannels underpin the control of hemostasis and thrombosis and represent potential therapeutic targets.